The Effect of the Jigsaw Cooperative Learning Model on Elementary Students’ Learning Outcomes in Islamic Religious Education - Abdurrahman Hilabi; Reni Puspita Sari; Miftahul Ulum; Durrul Isnaini (Jurnal Simki Postgraduate, 2025)
This study aimed to examine the effect of the Jigsaw cooperative learning model on students’ learning outcomes in Islamic Religious Education (PAI) at the elementary school level. The study employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The sample consisted of 24 fourth-grade students selected through total sampling. Data were collected using a 20-item multiple-choice achievement test that had been validated through expert judgement and empirical testing. The instrument demonstrated high reliability with a Cronbach’s Alpha coefficient of 0.82. Data were analysed using descriptive statistics, The Shapiro–Wilk normality test, the paired sample t-test, effect size (Cohen’s d), and normalised gain (N-Gain). The results showed a significant improvement in students’ learning outcomes, with the mean score increasing from 68.75 (SD = 7.11) in the pretest to 89.17 (SD = 7.76) in the posttest. The paired sample t-test revealed a statistically significant difference, t(23) = 9.60, p < .001. The effect size was enormous (Cohen’s d = 1.96), indicating a strong practical impact of the intervention. Furthermore, the N-Gain score was 0.65, categorised as moderate-to-high improvement. These findings indicate that the Jigsaw cooperative learning model significantly and practically enhances students’ cognitive learning outcomes and supports the implementation of student-centred learning in elementary Islamic Religious Education.